A INOVAÇÃO E O DESENVOLVIMENTO DE COMPETÊNCIAS EM GESTÃO EDUCACIONAL: O CASO REDE SINODAL DE EDUCAÇÃO - Evangelista, Mario L. S.; Sträher, André; Griebler, Gustavo (Salão do Conhecimento, 2013)
Resumo